Correlation between Hypertension and the Severity of Diabetic Retinopathy in Diabetes Mellitus Patients at Waled Regional General Hospital: A Cross-Sectional Study - Syifa Khaerunisa Trinanda; Boyke Sisprihattono; Widi Astuti (GHMJ (Global Health Management Journal))
Background: Diabetes mellitus is a metabolic disorder characterized by elevated blood sugar levels and resulting from deviations in either insulin secretion, insulin action, or both. Prolonged hyperglycemia can lead to various complications, including diabetic retinopathy. The main risk factors for developing diabetic retinopathy are uncontrolled diabetes mellitus, hypertension, and dyslipidemia.